Tools for monitoring aquatic environments to identify anthropic effects - da Rocha, Monyque Palagano; Dourado, Priscila Leocadia Rosa [UNESP]; Cardoso, Claudia Andrea Lima; Cândido, Liliam Silva; Pereira, Joelson Gonçalves; de Oliveira, Kelly Mari Pires; Grisolia, Alexeia Barufatti (Springer Nature, 2018)
Anthropic activities are directly related to the contamination of aquatic ecosystems owing to the release of numerous chemicals from agricultural and urban waste. These contaminants cause environmental degradation and a decrease in the availability of water quality. The objective of this search was to evaluate the efficiency of physicochemical, chemical, and microbiological tests; extraction of chlorophyll a; and genetic parameters to identify anthropic activities and weather condition effects on the stream water quality and the consequences of its use by the population. The physicochemical parameters were within the limits allowed by the Brazilian law. However, contamination by metals (Cd 0.510 mg L−1, Co 0.405 mg L−1, and Ni 0.316 mg L−1) has been found at various collection points to be more than the allowable values. The antibiotic oxytetracycline was detected in stream water in quantities of up to 89 μg L−1. In relation to microbiological contamination, Escherichia coli and Pseudomonas spp. have been isolated. The averages of chlorophyll a were up to 0.15558 mg cm−2. Genetic tools identified greater number of micronuclei and DNA damage in periods that showed lower rainfall rates and lower amounts of metals. The analysis used for monitoring was efficient to verify the interference that animal breeding and planting of different cultures have caused on that stream. Thus, the continued use of this water for drinking, irrigation of vegetables, and recreational activities makes the population susceptible to contamination by bacteria and creates conditions for the development of genetic alterations in the long run.
Keywords: Environmental pollutants; Genetic parameter; Microbiology; Surface water